2009
DOI: 10.1097/scs.0b013e3181a2d9aa
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Borne Palatal Distraction to Correct the Constricted Cleft Maxilla

Abstract: Rapid palatal expansion using a bone-borne distraction device in cleft patients with transverse maxillary hypoplasia who have failed nonsurgical orthodontic expansion provides adequate expansion necessary for alveolar bone grafting and stable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Vyas et al reported that the use of microimplant-assisted palatal distraction as an adjunct to SARPE provided adequate stable skeletal expansion [28]. Even though clinically they could achieve the skeletal expansion, the complex loading pattern and the biomechanical effects of this bone-borne palatal expander on the maxillary bone and the circum-maxillary sutures have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Vyas et al reported that the use of microimplant-assisted palatal distraction as an adjunct to SARPE provided adequate stable skeletal expansion [28]. Even though clinically they could achieve the skeletal expansion, the complex loading pattern and the biomechanical effects of this bone-borne palatal expander on the maxillary bone and the circum-maxillary sutures have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…SARME has recently been replaced by transpalatal distraction with superior results 5,9,11,19 . According to MOMMAERTS 12 conventional tooth-borne appliances produce greater loss of anchorage and more skeletal relapse during and after expansion.…”
Section: Discussionmentioning
confidence: 98%
“…Surgically assisted rapid maxillary expansion (SARME) has been proposed to produce better treatment results in adults and to prevent complications by surgically releasing the closed sutures resisting the expansion forces 1,17,19 . SARME has recently been replaced by transpalatal distraction with superior results 5,9,11,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence of the collapse and alveolar bone effects are among the reported complications (Gunbay et al 2008a;Mommaerts, 1999;Suri & Taneja, 2008). Transverse maxillary expansion with a bone-borne transpalatal distractor has been used with favourable results in congenital and acquired transverse maxillary deficiency (Gunbay et al 2008a;Koudstaal et al, 2006;Mommaerts, 1999;Suri & Taneja, 2008;Vyas et al 2009). In many studies, effects of transversal expansion have been examined by posteroanterior cephalometric measurements in dentoalveolar, maxillary base and nasal regions.…”
Section: Transpalatal Distraction Osteogenesis (Tpdo)mentioning
confidence: 99%